2022
DOI: 10.1101/2022.06.21.497048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter and literacy: a dynamic system in flux

Abstract: Past studies have linked differences in white matter tissue properties to reading skills. However, these studies have reported a range of, sometimes conflicting, results. Some studies suggest that white matter properties act as individual-level traits predictive of reading skill, whereas others suggest that reading skill and white matter develop as a function of an individual's educational context. In the present study, we tested two hypotheses: a) that diffusion properties of the white matter reflect stable b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 101 publications
4
11
2
Order By: Relevance
“…We hypothesized that fixel-based metrics would be sensitive to variation in reading abilities especially in the left arcuate fasciculus, left inferior fronto-occipital fasciculus, and cerebellum. Unlike recent cross-sectional studies of fractional anisotropy that yielded few-to-no regions exhibiting significant FA-reading relationships or group differences in FA ( Moreau et al, 2018 ; Koirala et al, 2021 ; Economou et al, 2022 ; Meisler and Gabrieli, 2022 ; Roy et al, 2022 ), we found that higher FDC related to better single-word reading skills throughout the brain. However, FDC did not differ between those with and without reading disabilities.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that fixel-based metrics would be sensitive to variation in reading abilities especially in the left arcuate fasciculus, left inferior fronto-occipital fasciculus, and cerebellum. Unlike recent cross-sectional studies of fractional anisotropy that yielded few-to-no regions exhibiting significant FA-reading relationships or group differences in FA ( Moreau et al, 2018 ; Koirala et al, 2021 ; Economou et al, 2022 ; Meisler and Gabrieli, 2022 ; Roy et al, 2022 ), we found that higher FDC related to better single-word reading skills throughout the brain. However, FDC did not differ between those with and without reading disabilities.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that phonological skills, as opposed to lower-level visual and orthographic processing, may provide more of a bottleneck to single-word reading abilities in children. The present results are supported by a large-scale longitudinal study finding that fractional anisotropy of the left AF, but not ILF, covaries with single-word reading skill trajectories in children (Roy et al, 2022). This notion is also consistent with a behavioral study demonstrating that orthographic skills are more related with the ability to read longer passages, as opposed to single words (Barker et al, 1992).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations